Effect of Aloe Vera Gel in the Healing of Post Operating Incissions: Evidence Based Nursing - Sitti Syabariyah; Belinda Rizky Amalia; Nina Gartika (Journal of Health Sciences and Medical Development, 2022)
The incidence of injuries in the world throughout the year is increasing, both acute and chronic wounds. In Indonesia, the prevalence of incisional wounds is 8.2%. Wound healing can be assisted with herbal plants, one of which is aloe vera. The purpose of this evidence-based nursing study was to determine aloe vera's effectiveness in the healing process of incisional wounds. The method used is a literature review. Database searches were conducted through Pubmed, Science Direct, Science Open and Google Scholar. The inclusion criteria of the journal in this study were journals that examined incisions, cuts or surgical wounds given intervention using aloe vera in a quasi-experimental research design, case study, double-blind, controlled trial, journals published in 2016-2021 and used Indonesian or English. This study's results indicate an influence of aloe vera in the wound-healing process, especially in the proliferative phase. This literature study can be used as evidence-based nursing at the level of nursing health services, especially wound care management based on aloe vera.